Building intelligent integrated management system based on Internet of things and edge computing and its application - Haiying SONG; Zhiwen CHEN; Baiping QIU; Fuhua KUANG; Shijun DENG (物联网学报)
In order to meet the needs of the intelligent management of modern commercial buildings,with the Internet of things (IoT) and edge computing technology,the intelligent building management system (IBMS) was developed based on ubiquitous building IoT by using the self-developed IoT gateway.The ubiquitous IoT eliminated the boundaries between the traditional building automation and information automation systems.The edge computing technology was used in the integrated management system to enhance the on-site decision-making ability and response speed of IBMS.The architecture of the integrated management system and the implementation of edge computing were discussed.The application of the system in the Shenzhen Dashi intelligent building shows the feasibility and effectiveness of the intelligent integrated management system based on ubiquitous building IoT.